The Reform of Tax Administration - Pellechio, Anthony; Tanzi, Vito. (Washington, D.C. : International Monetary Fund, 1995)
Tax administration plays a crucial role In determining a country's real (or effective) tax system. Unfortunately, tax administrations in many countries do not function optimally and distort the intention of tax laws. In order for taxation to have its intended effect on the allocation of resources, the distribution of income, and macroeconomic stability and growth, the tax administration must function effectively and efficiently. This paper addresses tax administration reform by describing briefly the causes for inefficient tax administration, identifying the essential elements of successful reform, and presenting measures to improve the tax administration. The common thread of a reform strategy is to focus administrative resources on problems in the tax collection system through promotion of voluntary taxpayer compliance and adoption of a logical sequence of procedures for efficiently identifying and handling instances of noncompliance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet